The experiences of selected Filipino public schools district supervisors in the implementation of the rationalization program - Manio, Bernabeth; Ancho, Inero (Faculty of Administrative Science and Policy Studies, 2023)
This study aimed to explore the experiences of selected public schools district supervisors in a schools division in the Philippines in the implementation of the Rationalization Program. The researchers employed qualitative-phenomenological study wherein 10 public schools district supervisors were purposely selected as participants of the study. To gather data, the researchers used validated semi-structured interview guide questions. The data that were collected were subjected to thematic analysis using six phases of Braun and Clarke (2013). Results show that PSDSs experiences in the Rationalization were summarized as follows: confusing and challenging experiences, experiences lapses in management of resources and fulfilling experiences. The study will have implications on the improvement of policies related to rationalization.